Studies of photoactive states of isovalently doped ZnSe crystals by the method of scanning photodielectric spectroscopy - Ryzhikov, V.; Starzhinskiy, N.; Chujai, O.; Migal, V.; Komar, V.; Katrunov, K.; Oleinik, S.; Zenya, I. (Functional Materials, 2004)
Using methods of photodielectric spectroscopy, studies have been carried out of the energy level structure of the defect complexes in isovalently doped zinc selenide crystals. On variation of light wavelength (λ), small changes in effective values of the real λ' and imaginary є'' parts of complex dielectric permittivity were measured in the low frequency (1-50 kHz) region using a high sensitivity AC bridge. Different configurations were used of electric and light fields in the crystals. The local energy level spectrum was determined from ε′(λ)-ε′′(λ) diagrams presented in the complex plane. Analysis has been carried out of relationship between characteristic features of these diagrams and parameters of photoactive states of different nature. Effects are discussed of the surface potential and band bending upon energetics of the local states. Методами фотодиэлектрической спектроскопии проведены исследования структуры энергетических уровней дефектных комплексов в изовалентно легированных кристаллах селенида цинка. При варьировании длины волны света (λ) с помощью высокочувствительных мостов переменного тока измерены малые изменения эффективных значений действительной λ' и мнимой λ'' частей комплексной диэлектрической проницаемости образцов в низкочастотной (1-50 кГц) области. Использовались различные конфигурации электрических и световых полей в кристаллах. Спектр локальных энергетических уровней определялся из диаграмм ε′(λ)-ε′′(λ), представленных в комплексной плоскости. Выполнен анализ связи характерных особенностей диаграмм с параметрами фотоактивных состояний различной природы. Обсуждается влияние поверхностного потенциала и изгиба зон на энергетику локальных состояний. Методами Фотодієлєктричної спектроскопи проведено досліджєння структури енергетичних рівнів дефектних комплексів в ізовалентно легованих кристалах селеніду цинку. При варіюванні довжини хвилі світла (λ) за допомогою високочутливих мостів змінного струму виміряно малі зміни ефективних значень дійсної λ' та уявної λ" частин комплексної діелектричної проникності зразків у низькочастотному (1-50 кГц) діапазоні. Використовувалися різні конфігурації електричних та світлових полів у кристалах. Спектр локальних енергетичних рівнів визначався із діаграм ε′(λ)-ε′′(λ), наведених у комплексній площині. Зроблено аналіз зв’язку характерних особливостей діаграм з параметрами фотоактивних станів різної природи. Обговорюється вплив поверхневого потенціалу та вигину зон на енергетику локальних станів.